Der Schatz in irdenen Gefäßen (2Kor 4,7): Existentiale Interpretation im 2. Korintherbrief? - Gräßer, Erich (Zeitschrift für Theologie und Kirche, 2000)
Rudolf Bultmann was always especially fond of the lecture on 2 Corinthians, since it was here that he found the existential interpretation to which he adhered: the interpretation of Christ's message in terms of human existence.